2017
DOI: 10.3892/ijmm.2017.3249
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor activation influences the ERK pathway and protects against neurological deficits and neuronal death

Abstract: Previous studies have demonstrated that global cerebral ischemia (GCI) causes neurological deficits and neuronal cell apoptosis. Calcitriol, a biologically active metabolite of vitamin D, exerts its endocrinological influence via nuclear vitamin D receptor. It is being assessed as an emerging therapeutic strategy in models of various medical conditions, including acute brain injury. The purpose of the present study was to investigate the neuroprotective effects of calcitriol on GCI and further refine the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The beneficial effects of VitD on central nervous system have been observed in animal models or clinical patients with neuropsychiatric disease, including Alzheimer's disease, Parkinson's syndrome, cerebral ischemia and multiple sclerosis [11,29,30]. In our recent researches [13,21], we also found that calcitriol, the active metabolite of VitD, is effective in the prevention of oxidative stress and apoptosis progression induced by traumatic brain injury. These results are in accordance with our findings, further lending weight to the hypothesis that VitD is likely to preserve neurological function in the context of hypertension.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The beneficial effects of VitD on central nervous system have been observed in animal models or clinical patients with neuropsychiatric disease, including Alzheimer's disease, Parkinson's syndrome, cerebral ischemia and multiple sclerosis [11,29,30]. In our recent researches [13,21], we also found that calcitriol, the active metabolite of VitD, is effective in the prevention of oxidative stress and apoptosis progression induced by traumatic brain injury. These results are in accordance with our findings, further lending weight to the hypothesis that VitD is likely to preserve neurological function in the context of hypertension.…”
Section: Discussionmentioning
confidence: 93%
“…For nissl staining, brain paraffin tissues were sectioned with 20 μm thickness, which were immersed in cresyl violet (0.1%), rinsed in distilled water, and differentiated in 95% ethyl alcohol. The presence of apoptosis was assessed by the terminal deoxynucleotidyl transferase-mediated FITC-dUTP nick end labeling (Tunel) method, which detects fragmentation of DNA in the nucleus during apoptotic cell death in situ [21]. The apoptosis detection assay was performed using a commercially available kit following the manufacturer's protocol (Keygen Biotech, Nanjing, China).…”
Section: Methodsmentioning
confidence: 99%
“…Total protein, nucleoprotein and cytoplasmic protein were extracted from brain tissues as previously described (19). The concentration of protein was measured using the bicinchoninic acid protein assay (Nanjing Jiancheng Bioengineering Institute, Nanjing, China).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, serum parathyroid hormone and alkaline phosphatase must be taken into account when considering vitamin D metabolism [49,50]. Furthermore, vitamin D receptor gene polymorphism may protect against neurological deficits and neuronal death, however, we did not test vitamin D receptor activation in our study [51]. Third, we did not classify SVD into different types according to STRIVE such as lacunes, WMHs, CMBs or PVS [8,52], and we did not assess the total SVD burden (0 to 4) [10].…”
Section: Discussionmentioning
confidence: 95%